Texture modulation of starch-based materials using microfoaming-assisted 3D printing - Robert Fribus; Jana Kant; Ahmed Raouf Fahmy; Mario Jekle (Future Foods, 2024)
Additive manufacturing has transformed the digital fabrication of foods, allowing the design and modulation of textural properties. However, modulation beyond the printer's resolution is still limited for generating various textures. Therefore, a microfoaming-assisted additive manufacturing approach for starch-based printing materials based on chemical leavening agents was developed. The applicability of three leavening agent systems, namely glucono-delta-lactone (GDL), monocalcium phosphate (MCP), sodium acid pyrophosphate (SAPP), alongside sodium bicarbonate (NaHCO3) was investigated. Their impact on printing behavior, geometrical stability, porosity, and textural properties of open-cell foam structures was elucidated. This study revealed that continuous release kinetics such as GDL-based systems, resulted in printing defects including line breakage and geometric expansion. Leavening agent systems with release temperatures above the applied temperature for 3D printing (MCP and SAPP-based systems) showed no significant deviations in 3D printing behavior, demonstrating their suitability for 3D printing. Performed double compression tests revealed substantial modulations in textural properties ranging from a 2.79-fold hardness reduction for SAPP at a concentration level of 2 % up to 10.2-fold reduction for 2 % GDL formulations compared to the unleavened reference. This study contributes to the understanding of various leavening agent kinetics for 3D food printing, providing new possibilities for food texture design.